Mechanisms of ROS Regulation of Plant Development and Stress Responses - Huang, Honglin; Ullah, Farhan; Zhou, Dao-Xiu; Yi, Ming; Zhao, Yu (Frontiers in Plant Science, 2019)
Plants are subjected to various environmental stresses throughout their life cycle. Reactive oxygen species (ROS) play important roles in maintaining normal plant growth, and improving their tolerance to stress. This review describes the production and removal of ROS in plants, summarizes recent progress in understanding the role of ROS during plant vegetative apical meristem development, organogenesis, and abiotic stress responses, and some novel findings in recent years are discussed. More importantly, interplay between ROS and epigenetic modifications in regulating gene expression is specifically discussed. To summarize, plants integrate ROS with genetic, epigenetic, hormones and external signals to promote development and environmental adaptation.